Developing Universal Influenza Vaccines: Hitting the Nail, Not Just on the Head - Lidewij C. M. Wiersma; Guus F. Rimmelzwaan; Rory D. de Vries (Vaccines, 2015)
Influenza viruses have a huge impact on public health. Current influenza vaccines need to be updated annually and protect poorly against antigenic drift variants or novel emerging subtypes. Vaccination against influenza can be improved in two important ways, either by inducing more broadly protective immune responses or by decreasing the time of vaccine production, which is relevant especially during a pandemic outbreak. In this review, we outline the current efforts to develop so-called “universal influenza vaccines”, describing antigens that may induce broadly protective immunity and novel vaccine production platforms that facilitate timely availability of vaccines.